Bibliometric Study on the Mapping of Qur'an and Health Studies Development in the Scopus Database - Nisa, Fathimah Khoirun; Nurrohim, Ahmad; Apriantoro, Muhamad Subhi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to determine the mapping of the development and direction of the Qur'an and Health research in Scopus-indexed publications. This study uses bibliometric analysis techniques to explore all publications indexed in the Scopus database on the Qur'an and Health from 1981 to 2023. The data obtained were analyzed using Excel and R / R-Studio. VOSviewer was used to visually analyze the emergence of keywords and document citations simultaneously. The author found 238 publications that fit the function, subject, and criteria set. The results of this study show an annual growth rate of 5.88%, with the most publications on the Qur'an and Health in 2020. Malaysia is the country that contributes the most publications affiliated with the International Islamic University Malaysia. Abooul-Enein, BH, Al-Rowais, N., and Isgandarova, N. are the most productive authors on the theme of the Qur'an and Health. The bibliometric analysis conducted is limited to Scopus data. Other national and international databases are not considered in this study. This study presents a brief overview of the literature accessible to researchers in the Quran and the health field.